menanamkan nilai kesetiakawanan sosial sejak dini pada anak - tyas eko raharjo (Media Informasi Penelitian Kesejahteraan Sosial, 2020)
abstractThis study aims to describe the planting of the value of social solidarity early on in children in the family. The approach used is descriptive qualitative to reveal the instillation of the value of social solidarity in children in the family. The study was conducted in the Village of Panggungharjo, Sewon District, Bantul Regency with the setting of a family family that has elementary school age children. Panggungharjo Village was chosen as a research location because it is unique in the organization of social welfare services, especially in preserving local culture that is related to children's traditional games. The village government also provides a location for implementing traditional children's games called Kampong Dolanan. The data source was determined purposively namely the village apparatus and the community of Desa Panggungharjo. Data obtained using interview techniques, observation, and document review, then the data are analyzed descriptively with exposure in the form of narration.The results showed that the attention of the village government in instilling the value of social solidarity for children was very good with the availability of kampong dolanan as a means of playing children and socializing with their peers. The existence of the traditional playground is a means of growing social solidarity values for children. Instilling the value of social solidarity by parents by providing understanding and exemplary children in life in the family. It is recommended to local governments to conduct guidance and outreach to teaching staff related to the value of social solidarity in schools, then the teaching staff can help direct their students to understand, and behave according to the values of social solidarity.